2012
DOI: 10.2106/jbjs.k.00471
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Preparation Solutions in Lumbar Spine Surgery

Abstract: ChloraPrep and DuraPrep are equally effective skin-preparation solutions for eradication of common bacterial pathogens on the skin overlying the lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 14 publications
2
52
2
3
Order By: Relevance
“…This result is consistent with previous observations in the shoulder 10,40,45,46 and in the spine 41 . Propionibacterium usually did not grow on culture of dermal specimens from female subjects whereas dermal cultures were commonly positive for male patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with previous observations in the shoulder 10,40,45,46 and in the spine 41 . Propionibacterium usually did not grow on culture of dermal specimens from female subjects whereas dermal cultures were commonly positive for male patients.…”
Section: Discussionsupporting
confidence: 94%
“…It is commonly assumed that the patient's epidermal skin surface is the source of the Propionibacterium grown on culture of specimens from infected orthopaedic implant sites. Unfortunately, presurgical skin surface preparations do not completely eliminate Propionibacterium [39][40][41][42] , perhaps because the organism is sheltered in dermal sebaceous glands, each of which may harbor as many as 10 5 Propionibacterium organisms per follicle 43 . Surgical incisions transect the sebaceous glands, after which these organisms may Disclosure: One or more of the authors received payments or services, either directly or indirectly (i.e., via his or her institution), from a third party in support of an aspect of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…12,56,57 Savage et al 12 reported 100 consecutive lumbar spinal surgery patients, finding no differences between ChloraPrep (2% CHG and 70% isopropyl alcohol; Enturia, El Paso, Texas) and DuraPrep (0.7% available iodine and 74% isopropyl alcohol; 3M Healthcare, St. Paul, Minnesota) in the rate of positive culture results after skin preparation.…”
Section: Skin Antisepsismentioning
confidence: 99%
“…Although the most common skin bacteria are coagulasenegative Staphylococcus, Propionibacterium acnes (P. acnes), and Corynebacterium, 12 the most frequent pathogen that causes SSI is Staphylococcus aureus, 13 which accounts for approximately 50% of all SSIs.…”
mentioning
confidence: 99%